Determination of Volatile Organic Compounds in Selected Strains of Cyanobacteria. (19th February 2015) - Milovanović, Ivan; Mišan, Aleksandra; Simeunović, Jelica; Kovač, Dajana; Jambrec, Dubravka; Mandić, Anamarija
Abstract : Microalgal biomass can be used in creating various functional food and feed products, but certain species of microalgae and cyanobacteria are known to produce various compounds causing off-flavour. In this work, we investigated selected cyanobacterial strains of Spirulina, Anabaena, and Nostoc genera originating from Serbia, with the aim of determining the chemical profile of volatile organic compounds produced by these organisms. Additionally, the influence of nitrogen level during growth on the production of volatile compounds was investigated for Nostoc and Anabaena strains. In addition, multivariate techniques, namely, principal component analysis (PCA) and hierarchical cluster analysis (HCA), were used for making distinction among different microalgal strains. The results show that the main volatile compounds in these species are medium chain length alkanes, but other odorous compounds such as 2-methylisoborneol (0.51–4.48%), 2-pentylfuran (0.72–8.98%), β -cyclocitral (0.00–1.17%), and β -ionone (1.15–2.72%) were also detected in the samples. Addition of nitrogen to growth medium was shown to negatively affect the production of 2-methylisoborneol, while geosmin was not detected in any of the analyzed samples, which indicates that the manipulation of growth conditions may be useful in reducing levels of some unwanted odor-causing components.